Effects of strain rate and temperature on the interface deformation mechanism of Cu/Al4Cu9/Al2Cu/Al multilayer composites: A molecular dynamic study - Hui Zhang; Aiqin Wang; Aiqiong Pan; Jingpei Xie (Journal of Materials Research and Technology, 2025)
This study employed molecular dynamics simulations to investigate the effects of strain rate and temperature on the interface deformation mechanisms of Cu/Al4Cu9/Al2Cu/Al multilayer composites under uniaxial tensile loading. Results revealed that the microscopic plastic deformation mechanisms and mechanical properties were highly sensitive to temperature and strain rate. While the strain rate negligibly influenced the Young's modulus, higher rates enhanced both tensile strength and fracture strain. Conversely, elevated temperatures gradually reduced Young's modulus, tensile strength, and fracture strain.Given the similar deformation processes across conditions, a representative model (300 K, strain rate 10−9/s) was selected for detailed interface deformation analysis.The primary deformation mechanism involved confined dislocation slip and twinning within layers. The Al2Cu layer exhibited localized strain concentration, initiating crack propagation, whereas the Al4Cu9 layer demonstrated dislocation slip and superior cooperative deformation capability. Increased strain rates promoted dislocation accumulation, strengthening deformation resistance, while higher temperatures reduced dislocation density, weakening interfacial bonding and ductility.These findings provide theoretical guidance for optimizing copper-aluminum composites in engineering applications.